A photohistory of World War One - Haythornthwaite, Philip J. (London : Arms and Armour ; New York, NY : Sterling Pub. [distributor], 1995)
Photographs illustrate the history of the First World War.
"Originally published 1989-90 as five individual volumes in the fotofax series"--Title page verso
Includes bibliographical references.
Keywords: 1914-1918; World War, 1914-1918 -- Pictorial works; illustrated books; Illustrated works; Pictorial works; Illustrated works